New assessment of basement units in the fitz roy area: implications for an early mesozoic tectono-metamorphic event at southern patagonia - Suárez, Rodrigo Javier (2018)
Among the complex collage of metamorphic belts exposed in the Patagonian Andes, the Triassic metamorphic rocks are poorlyrepresented. They only outcrop at the southern Chilean coast within the Chonos Metamorphic Complex (CMC), a subductioncomplex (Hervé et al. 2008), which witness of an active subduction during the Late Triassic (Hervé and Fanning 2001). Recently,U-Pb dating in detrital zircons performed in metasedimentary rocks from the Nunatak Viedma, which crops out west of the Fitz Royarea, within the Southern Patagonian Ice Field, revealed grain-ages youngest at Late Triassic (Suárez et al. 2018). We proposedto define the Nunatak Viedma Unit (NVU) in the Southern Patagonian Andes (SPA; Suárez et al. 2018) on the basis of these newobservations. The rocks of the NVU exhibit a main phase of ductile to brittle-ductile deformation tentatively correlated with theLate Triassic-Early Jurassic Chonide deformation event (Suárez et al. 2018) identified in the southern Chilean coast (Thomson andHervé 2002; Hervé et al. 2008). However, the age of the NVU?s tectono-metamorphic event, as well as its tectonic significance, arestill unknown. New geological mapping carried out in the Fitz Roy region (Fig. 1) reveals that outcrops previously mapped either asBahía de la Lancha Formation (BLF) or as volcanic rocks of the El Quemado Complex, shows lithological and structural similaritieswith the rocks of the NVU (Fig. 1). The preliminary structural results presented in this contribution aim to better constrain thedeformation phase of the NVU and to discuss its age and tectonic significance.